How Institutional Evaluation Bridges Uncertainty and Happiness: A Study of Young Chinese People - Wu, Ying; Qin, Guangqiang; He, Chuanyi; Wang, Wenying (Frontiers in Psychology, 2021)
Uncertainty triggers negative psychological responses, while positive institutional evaluations elevate individuals’ sense of control and satisfy their need for structure and order. Data from the 2015 Chinese Social Survey (N=4,605) demonstrated that objective uncertainty negatively predicted the happiness of young people (aged 18–45 years), but this negative relationship was attenuated among those who evaluated the institutional system (e.g., social security, local government effectiveness, and trust in government) positively—that is, positive institutional evaluation may have protected people’s happiness from the threat of uncertainty. In addition, participants from different age groups evaluated the institutional system differently. As the first generation born after the Chinese economic reform, young people born in the 1980s (aged 26–35 years) had unique experiences compared to preceding (aged 36–45 years, born in the 1970s) and succeeding (aged 18–25 years, born in the 1990s) generations. Among the three age groups, young people born in the 1980s held the least positive evaluation of the institutional system. Institutional evaluation also showed the weakest moderating effect on this group’s happiness.